On commercial panics - Lawson, James A. (Statistical and Social Inquiry Society of Ireland, 1849)
Amongst the many subjects of inquiry which present themselves in the wide field of Statistics, there is none, I think, more calculated to excite our interest, than the one which I am about to bring under the consideration of the Society, and which is so well known in the mercantile world under the name of Commercial Panic or Crisis. If it be difficult to ascertain the laws which regulate commercial matters under ordinary circumstances, surely the extraordinary or anomalous ones challenge our most careful consideration.
Commercial panics
Read May 15th 1848
Keywords: Commercial crises; Speculative dealing; 314.15